(a) (2x + 3y/4)^{2 }

(b) (4x^{2} + 5y^{2}) (4x^{2} – 5y^{2})

(c) (x + 2/5) (x – 2/5)

(d) (xy – 2z)^{2 }

(e) (a + bc) (a – bc) (a^{2} + b^{2}c^{2})

(f) (2a/3b – 3b/2a)^{2 }

(g) (- 3a – 4b)^{2 }

(h) (a – 7) (a + 7)

(a) (2x + 3y/4)^{2 }

(b) (4x^{2} + 5y^{2}) (4x^{2} – 5y^{2})

(c) (x + 2/5) (x – 2/5)

(d) (xy – 2z)^{2 }

(e) (a + bc) (a – bc) (a^{2} + b^{2}c^{2})

(f) (2a/3b – 3b/2a)^{2 }

(g) (- 3a – 4b)^{2 }

(h) (a – 7) (a + 7)

Answer Gyaan © 2023

Solution :(a) (2x + 3y/4)^{2}= (2x)

^{2}+ 2.2x. 3y/4 + (3y/4)^{2}= 4x

^{2}+ 3xy + 9y^{2}/16(b) (4x^{2}+ 5y^{2}) (4x^{2}– 5y^{2})= (4x

^{2})^{2}– 5y)^{2}= 16x

^{4}– 25y^{4}(c) (x + 2/5) (x – 2/5)= x

^{2}– (2/5)^{2}= x

^{2}– 4/25(d) (xy – 2z)^{2}= (xy)

^{2}– 2.x.y (+ 2z) + (2z)^{2}= x

^{2}y^{2}– 4xy^{2}+4z^{2}(e) (a + bc) (a – bc) (a^{2}+ b^{2}c^{2})= (a

^{2}– b^{2}c^{2}) (a^{2}+ b^{2}c^{2})= (a2)

^{2}– (b^{2}c^{2})= a

^{4}– b4c^{4}(f) (2a/3b – 3b/2a)^{2}= (2a/3b)

^{2}– 2 2a/3b 3b/2a= 4a

^{2}/9b^{2}– 2 + 9b^{2}/4a^{2}(g) (- 3a – 4b)^{2}= [(- 3a + 4b)]

^{2}– (3a + 4b)= (3a)

^{2}+ 3a.4b + (4b)^{2}= 9a

^{2}+ 24ab + 16b^{2}(h) (a – 7) (a + 7)= a

^{2}– (7)^{2}= a

^{2}– 49